Deep Vein Thrombosis among Intensive Care Unit Patients; an Epidemiologic Study - Miri, Mir Mohammad; Goharani, Reza; Sistanizad, Mohammad (Archives of Academic Emergency Medicine, 2017)
Introduction: Deep vein thrombosis (DVT) is a major cause of morbidity and mortality in intensive care unit (ICU) patients despite use of prophylactic anticoagulant therapy. The aim of the present study was to determine the incidence of DVT among medical and surgical ICU patients. Methods: In this cross sectional study, patients older than 18 years who were hospitalized in the ICU of Imam Hossein educational Hospital, Tehran, Iran, for ≥ 2 days, during August 2008 to July 2011 were evaluated regarding DVT incidence. Demographic data, comorbidities, acute physiology and chronic health evaluation (APACHE) II scores, ICU length of stay, type of DVT prophylaxis, and patient outcomes were analyzed using SPSS 19. Results: Out of the 1387 reviewed patient files, 500 (36.04%) patients had been classified as potential DVT cases. DVT occurred in 3.5% of them with the mean age of 60 ± 18 years (62.5% male) and mortality rate of 27.1%. Significant independent risk factors of DVT incidence were age (p = 0.02) and length of ICU stay (p = 0.01). Conclusion: The results of this study showed the 3.5% incidence of DVT in ICU admitted patients. Longer ICU stay and older age were independent risk factors of DVT development.